Ventilation and gas exchange during sustained exercise at normal and raised CO2 in man. - Pandit, J; Robbins, P (1992)
Five subjects underwent each of three protocols for 43 min: (A) at rest; end-tidal PCO2 was held constant at 2-5 Torr above resting values; (B) during 70 Watt bicycle exercise; PETCO2 was uncontrolled; (C) during 70 Watt exercise; PETCO2 was held 2-5 Torr above exercising values. During all protocols, end-tidal PO2 (PETO2) was held at 100 Torr. The first 5 min of each protocol were excluded from data analysis to approach a steady state, and the remaining 38 min analysed to determine whether any trends were present. At rest, ventilation did not change over the 38 min period. However, during hypercapnic exercise (protocol C), ventilation rose significantly by a mean +/- SE of 4.9 +/- 0.8 L/min (P less than 0.01) over the 38 min period. In protocol B, ventilation was lower than in protocol C, but did not change over the 38 min period. However, PETCO2 fell significantly by a mean of 0.65 +/- 0.05 Torr (P less than 0.01). This change in PETCO2 was due to a significant fall in the respiratory quotient (mean = -0.05 +/- 0.01, P less than 0.01) and metabolic CO2 production (mean = -0.06 +/- 0.01 L/min, P less than 0.01). The fall in respiratory quotient implies a change in metabolic substrate during exercise. Furthermore, the results suggest that ventilation is not always matched closely to metabolic CO2 production during exercise.